2000
DOI: 10.1034/j.1399-6576.2000.440821.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine poisoning: report of two cases

Abstract: Two patients intentionally took chloroquine in overdose for different purposes. The first patient took chloroquine 2.7 g to terminate her pregnancy and the second patient took 3.75 g to terminate his life. The management of these two patients mainly consisted of gastric lavage, activated charcoal, ventilation, diazepam and inotropic support. The effect of chloroquine on the myocardium is discussed and the role of chloroquine as an abortifacient is reviewed. Hypokalemia should be recognized early and treated ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The therapeutic dose range for children is 5-10 mg/kg (base) with a lethal dose of 30 -50 mg/kg (1,7,13,44,45). Clyde describes a 3-year-old boy on 150 mg of chloroquine base every week who died of cardiac arrest within 1 h of taking 300 mg (27 mg/kg), the lowest reported lethal dose (46).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The therapeutic dose range for children is 5-10 mg/kg (base) with a lethal dose of 30 -50 mg/kg (1,7,13,44,45). Clyde describes a 3-year-old boy on 150 mg of chloroquine base every week who died of cardiac arrest within 1 h of taking 300 mg (27 mg/kg), the lowest reported lethal dose (46).…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 This observation has been attributed to 'differential gender motivation', with Queen and colleagues 1 as well as other authors in Zimbabwe 4,16 suggesting that chloroquine was used by females as a method of abortion. Although chloroquine appears safe in pregnant women at doses used for prophylaxis, 17 there is a widespread belief in Zimbabwe 4,16 and elsewhere 18,19 that it is abortifacient, even though there is no published literature in humans to support this. In the present study, the relative risk of a woman admitted with chloroquine poisoning also being pregnant was calculated to be just over twice that of a woman admitted with any other drug poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…However, several reports have suggested that hypokalemia may be protective in severe CQ poisoning. 18 20 Therefore, replacement of potassium is controversial in the setting of acute toxicity, although we believe it would be reasonable to treat severe hypokalemia (i.e., < 2 mmol/L). Cases of rebound hyperkalemia have been reported once toxicity resolves; therefore, serial potassium levels should be obtained.…”
Section: Clinical Managementmentioning
confidence: 99%